1997
DOI: 10.1042/bj3230629
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the N-terminus of human factor IX by defective propeptide cleavage or acetylation results in a destabilized calcium-induced conformation: effects on phospholipid binding and activation by factor XIa

Abstract: The propeptide of human coagulation factor IX (FIX) directs the gamma-carboxylation of the first 12 glutamic acid residues of the mature protein into gamma-carboxyglutamic acid (Gla) residues. The propeptide is normally removed before secretion of FIX into the blood. However, mutation of Arg-4 in the propeptide abolishes propeptide cleavage and results in circulating profactor IX in the blood. We studied three such genetic variants, factor IX Boxtel (Arg-4-->Trp), factor IX Bendorf (Arg-4-->Leu) and factor IX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Our result shows that, compared to the wild-type reporter-protein, the R-1S and R-4Q mutants appear to be properly carboxylated, but migrate slower (Figure 5). This result suggests that mutations at -1 and -4 do not affect reporter-protein carboxylation but prevent the cleavage of the propeptide, which agrees with previous observations 29,30,34 .…”
Section: Effect Of Naturally Occurring Propeptide Mutations On Coagulsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result shows that, compared to the wild-type reporter-protein, the R-1S and R-4Q mutants appear to be properly carboxylated, but migrate slower (Figure 5). This result suggests that mutations at -1 and -4 do not affect reporter-protein carboxylation but prevent the cleavage of the propeptide, which agrees with previous observations 29,30,34 .…”
Section: Effect Of Naturally Occurring Propeptide Mutations On Coagulsupporting
confidence: 92%
“…Together, these results suggest that mutations at -9 and -10 of the propeptide are more sensitive to warfarin inhibition. 1 3 Naturally occurring mutations at position -4 and -1 of the propeptide preclude post-translational cleavage of the propeptide, resulting in secretion of the procoagulation factor with its propeptide still attached 29,30,34,35 . To examine the effect of these mutations on carboxylation, we mutated R-1 (R-1S) or R-4 (R-4Q) of the propeptide in our reporter-protein and transiently expressed them in HEK293 cells.…”
Section: Effect Of Naturally Occurring Propeptide Mutations On Coagulmentioning
confidence: 99%
“…It is also suggested that the Gla domain plays an important role in the activation of factor IX by factor XIa as well as in the binding to phospholipids. In fact, Wojcik et al (29) have provided evidence that the conformational change of Gla domain is important for the factor IX activation by factor XIa.…”
Section: Discussionmentioning
confidence: 99%
“…The noncatalytic portion of the molecule contains (from N terminus to C terminus) the Gla domain, a short aromatic stack region, two EGF-like domains, and the activation peptide (3). Some Gla domain mutations causing hemophilia B are associated with poor factor XIa mediated activation, as is the failure to remove the propeptide from the N terminus of the molecule (26,27). Similarly, single amino acid substitutions in the EGF-1 (factor IX New London) (51) and EGF-2 (52) domains associated with cross-reactive material-positive hemophilia B are activated poorly by factor XIa.…”
Section: Discussionmentioning
confidence: 99%
“…A Gla domain mutation at amino acid 4 associated with hemo-philia B interferes with factor XIa-mediated activation of FIX (26), as does failure to remove the FIX propeptide from the N terminus (27). Monoclonal antibodies directed against FIX-Gla block activation of FIX by factor XIa (28,29).…”
mentioning
confidence: 99%